Influence of planting arrangement and plant population on production of pineapple (Ananas comosus) - Cardinali, Lúcio Roscoe; Andersen, Otto (Pesquisa Agropecuaria Brasileira, 2014)
Plant population and planting arrangement in pineapples (Ananas comosus (L) Merr., var. Lagoa Santa) affected the components of yield in the following manner: 1) The total number of fruits harvested increased in direct proportion to increases in plant population within the limits studied (10,000 to 30,000 plants/ha). 2) Mean fruit weight was not significantly affected by population density although minor reductions in fruit weight occurred as plant population increased. 3) Total weight of fruit per unit area increased in direct proportion to increases in plant population. A yield increase of 460 kilograms/ha was obtained for each 1,000 plant increment in population density up to 30,000 plants/ha. 4) Planting arrangements which provided maximum distances between rows (0.75 m) and minimal distances between plane beds (1.25 m) significantly increased fruit number but did not significantly affect mean weight per fruit or total yield. 5) Earliness was not significantly affected bl planting arrangement or plant density. A slight but non-significant delay in harvest was observed with higher plant populations. 6) Plant population and planting arrangement did not significantly alter number of slips produced per plant. A spacing is recommended that provides for a minimum of 30,000 plants/ha with a distance of 1.50 m between plane beds and 0.50 m between rows in the beds and 0.33 m between plants in the row even though the trial showed a tendency for best results using a 1.25 m spacing between plane beds. This is because a spacing of 1.25 m is considered too narrow for the cultural practices utilized at the present time.